2007
DOI: 10.1002/hyp.6596
|View full text |Cite
|
Sign up to set email alerts
|

Processes affecting transfer of sediment and colloids, with associated phosphorus, from intensively farmed grasslands: a critical note on modelling of phosphorus transfers

Abstract: In this commentary we are concerned with mathematical models of phosphorus transfers from agricultural land, particularly intensive grassland, to receiving waters (Haygarth et al., 2006). We believe that the complexity of this problem requires an initially wide discussion of possible modelling concepts and the associated benefits or problems with these approaches. Hence we are reluctant to break the phosphorus-modelling problem down to smaller scales or detailed levels of complexity, e.g. sediments/colloids, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Thus, there will be an inevitable compromise between improvements and uncertainty in applications to those majority of sites that will not be data rich (Beven 2000(Beven , 2002. Krueger et al (2007) have suggested that problems of this type would require new modelling strategies within an uncertainty learning framework for improving phosphorus model development and evaluation. Importantly, we need to further investigate what is the correct balance between the process complexity of the models we develop with the quality and quantity of observations we will ever have to drive and evaluate models used to inform WFD policy decisions at national scales of interest.…”
Section: Wider Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, there will be an inevitable compromise between improvements and uncertainty in applications to those majority of sites that will not be data rich (Beven 2000(Beven , 2002. Krueger et al (2007) have suggested that problems of this type would require new modelling strategies within an uncertainty learning framework for improving phosphorus model development and evaluation. Importantly, we need to further investigate what is the correct balance between the process complexity of the models we develop with the quality and quantity of observations we will ever have to drive and evaluate models used to inform WFD policy decisions at national scales of interest.…”
Section: Wider Commentmentioning
confidence: 98%
“…It is important, therefore, that the uncertainties in model predictions are well understood. Therefore, estimating prediction uncertainties in water quality modelling is becoming increasingly appreciated (Krueger et al 2007;Page et al 2004Page et al , 2005Radwan et al 2004;Rode et al 2007;Singh et al 2007;van Griensven and Meixner 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is important to be the uncertainties in model predictions are well understood. Estimating prediction uncertainties in water quality modelling is becoming increasingly appreciated (Krueger et al, 2007;Page et al, 2004Page et al, , 2005Radwan et al, 2004;Rode et al, 2007;Singh et al, 2007;van Griensven and Meixner, 2006). While there are various methods available for quantifying the uncertainty in physical hydrologic models (Christiaens and Feyen, 2002;Beven and Binley, 1992), little discussion is found in literature regarding the uncertainty analysis of the ANN hydrologic models except a few (Kingston et al, 2005;Khan and Coulibali, 2006;Han et al, 2006;Srivastav et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reasons for revisiting model evaluation are discussed in Chapter 4, not least that iterative improvements of both models and techniques to evaluate models are vital if we are to develop better predictions of soil erosion. There is also a growing understanding amongst many environmental scientists that developing more robust analyses of model predictions requires an evaluation of the uncertainties involved in the modelling process (Beven & Freer, 2001;Krueger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Others have chosen to concentrate on the uncertainties in the data directly, for example using bootstrapping methods to assess rating curve and sediment load dynamics, showing considerable uncertainties in this information (Rustomji & Prosser, 2001). In a series of papers, Krueger et al (2007Krueger et al ( , 2009Krueger et al ( , 2010 demonstrate the importance of taking into account uncertainties in hydrological measurements as well as those associated with models. Hydrographs are not errorfree, and Krueger et al (2009) demonstrate that errors may be significant (see Section 5.4).…”
Section: Introductionmentioning
confidence: 99%